Perkembangan Pembelajaran IPS Pada Tingkat Sekolah Dasar - Mawarni, Iga; Rahmawati, Alfira; Salsabilah, Sifa Putri; Desilawati, Della; Jadidah, Ines Tasya (Indo-MathEdu Intellectuals Journal, 2024)
Social Studies education in Indonesia has emerged and evolved through several changes in accordance with the conditions of the Indonesian nation. The aim of this research is to understand the development of Social Studies learning at the Elementary School level from its inception until now. This research utilizes qualitative analysis techniques. Qualitative analysis is a data analysis process that does not involve numerical data, and generally, the results of qualitative analysis are subjective. The data collection method involves a literature review, where data is gathered by reading and analyzing literature that has been found and studied by other researchers. There are four stages of literature review in the research process: preparing the necessary tools, compiling a bibliography, organizing time, and reading or recording research materials. The literature obtained from various references is critically and deeply analyzed to support propositions and ideas. The results of data analysis indicate that the current development of Social Studies learning in Indonesia is not similar to the early introduction of Social Studies education in the country. The field of Social Studies entered Indonesia from the United States, where it is known as social studies. America is considered one of the countries with extensive experience and significant academic reputation in the field of Social Sciences